USING CORPORA IN LANGUAGE TEACHING - Toshpulatova, Mehriniso (Журнал иностранных языков и лингвистики, 2021)
Over the past yearss, corpora have not only revolutionized linguistic research but have also had an impact on second language learning and teaching. In the field of applied linguistics, more and more researchers and practitioners treasure what corpus linguistics has to offer to language pedagogy. Still, corpora and corpus tools have yet to be widely implemented in pedagogical contexts. The aim of this article is to provide an overview of pedagogical corpus applications and to review recent publications in the area of corpus linguistics and language teaching. It covers indirect corpus applications, as well as direct applications of corpora in the second language classroom.